Computed Tomography Evaluation of Mucosal Thickening of Maxillary Sinus in Relation to Sinus Outflow Obstruction - Pathak, Manish Raj; Gautam, Mahesh; Bhattarai, Manoj; Khadka, Roshana (Journal of Nobel Medical College, 2025)
Background: Maxillary sinus mucosal thickening is a common radiologic finding, often incidentally detected on computed tomography scans. Its relationship with sinus outflow obstruction remains clinically significant but underexplored.Materials and Methods: This prospective cross-sectional study was conducted at Birat Medical College Teaching Hospital over one year. A total of 106 patients undergoing CT scans of the paranasal sinuses were included based on the presence of mucosal thickening. Patients with facial trauma, suspected malignancy, or intubation were excluded. CT scans were analyzed for mucosal thickening patterns, grades, and presence of outflow obstruction. Statistical analysis was done using SPSS.Results: Out of 106 patients, 51.9% were female and 48.1% male. Headache (60.4%) was the most common presenting symptom. Circumferential thickening was the predominant pattern (42.5%), followed by polypoidal (27.4%), focal (18.9%), and complete opacification (11.3%). Outflow obstruction was present in 60.4% of cases. A statistically significant association was found between both the grade and pattern of mucosal thickening and sinus outflow obstruction (p < 0.001). Notably, higher grades (>15 mm) and complete/circumferential patterns had a stronger correlation with obstruction.Conclusion: Our study demonstrates a significant association between the grade and pattern of maxillary sinus mucosal thickening and sinus outflow obstruction on CT imaging. Higher grades of thickening, particularly those exceeding 15 mm, and complete or circumferential patterns, were more frequently associated with obstruction.